Structure Simulation & Modelling Using HFSS - Wan Hussain, Wan Hanafi (2018)
The fast development of mobile phone and other electronic products has occurred lately due to the high demand from the consumers. This situation has imposed more challenges to the designer to work more on the high frequency spectrum such as Radio Frequency (RF) sockets and it is not easy to design high frequency structure due to its small size. Before a new design of RF socket can be finalised, the response of the new design needs to be analysed first because the bad response produced will affect the performance of the RF socket. Currently, there are two methods that being used in industry to analyses the RF socket response which are through fabrication and simulation software. However, both existing methods are very time-consuming and costly to be done. Therefore, a new simple and cheap method of designing the RF socket is proposed in this project where by substituting the value of desired pitch only, the designer can get the response in short of time. To verify this method is correct and reliable to be used, a simple structure has been drawn and the response has been produced. The results obtained shown that the response from the polynomial equation is capable to give identical shape with the simulation result. The polynomial equations from the actual structure also has been derived in this project. The polynomial equation that has been derived is believed can ease the designer’s work as they do not have to start from the beginning if they want to change the pitch of the existing design. What they need to do is just plug in the value of pitch that they want into the polynomial equation and they will get the response straight away.